The changes of surgical treatment for symptomatic uterine myomas in the past 15 Years - Weihong Yang; Ning Luo; Lishan Ma; Hong Dai; Zhongping Cheng (Wolters Kluwer Medknow Publications, 2018)
Study Objective: The aim of this study is to elaborate the changes of the surgical approach of treatment for uterine myomas in Yangpu Hospital in the past 15 years. Design: This was retrospective cohort study. Setting: Yangpu Hospital, Tongji University School of Medicine, Shanghai, China. Materials and Methods: A total of 4113 patients with symptomatic uterine myomas underwent surgical treatments. Interventions: Eight kinds of different surgeries were involved in the study, including abdominal or laparoscopic surgery, hysterectomy, or uterus-sparing myomectomy. Measurements: The study collected patients' clinical data and reviewed surgical access and approach, complications, and the results of following up. Results: A total of 1559 cases (37.9%) underwent uterus-sparing myomectomy, 3005 cases (73.1%) performed laparoscopic surgeries. The percentage of laparoscopic surgery was significantly higher than homochronous data of laparotomy after 2003 (P < 0.001). The per year total of uterus-reserved surgery was proved to be negatively correlated with patient's age (R2 = 0.930; P < 0.001). The rate of myomas recurrence was significantly lower in the combined myomectomy and uterine artery occlusion group (4%, 34/910) than in the single myomectomy group (10.5%, 44/420) (P < 0.001). Conclusions: Retaining uterus and minimally invasive surgery were the important trends of surgical treatment for symptomatic uterine myomas. Laparoscopic uterus-sparing myomectomy may be an alternative to hysterectomy to manage to appropriate patients with uterine myomas.